PROTOTYPE APLIKASI CUSTOMER RELATIONSHIP MANAGEMENT (CRM) SEBAGAI PENINGKATAN MUTU LAYANAN DI UPN "VETERAN" JAKARTA - Izhar Yusuf Siregar (2020)
Information technology has developed rapidly since entering the era of the Industrial Revolution 4.0. no exception to competition between educational institutions such as State Universities (PTN) or Private Universities (PTS) in Indonesia. With the increasingly intense competition among tertiary institutions in Indonesia, all higher education institutions have to provide the best possible service to their students, either in providing adequate campus facilities or quality learning. One of the competition that occurs is in getting new students in large numbers and with quality. To achieve this goal, a good strategy and management of customer service is needed. Therefore, there is a need for communication between universities and their service users, for example students. One way that can be done is by applying the concept of Customer Relationship Management (CRM). Customer Relationship Management (CRM) can help universities, one of which is UPN "Veteran" Jakarta, which is a state university with a large number of service users to establish good relationships with its service users. One way to implement the CRM concept is to use a web application where the application can provide insight or information to users and improve customer relationships. The system is built in the form of web-based Electronic Customer Relationship Management (e-CRM) to improve the quality of UPN "Veteran" Jakarta services. With this application, it is expected that there will be a relationship between stakeholders, namely universities and customers, namely users of more communicative services.